DYNAMIC MODELS FOR HOT-EXTRUSION OF POLYESTER FIBRE - G. M. Irapetiants; M. M. Kozhevnikov; N. I. Ulianov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers modeling of dynamics on hot extrusion process for polyester fibre. New modifications of nonlinear dynamic models are have been proposed in the paper. The models in contrast with the known ones make it possible to take into account an effect of tensile stress magnitude and duration of its application on temperature of the hot extrusion, in order to achieve the desired values of strength and relative elongations of the polyester fibre. The proposed models are applicable for efficient solution of problems on synthesis of combined control systems for regulation of hot extrusion temperature.